N-Butyl Cyanoacrylate Glue Versus Nonspherical Polyvinyl Alcohol Particles For Prostatic Arterial Embolization To Treat Benign Prostatic Hyperplasia: Safety and Efficacy - Hijazi, Bilal Ahmad; Shi, Hai-Bin; Liu, Sheng; Alqurashi, Turki A.; Sabri, Zakir J. (Urology Journal, 2023)
Purpose: Our aim is to compare N-butyl cyanoacrylate (NBCA) glue and non-spherical polyvinyl alcohol (PVA) particles for prostatic artery embolization (PAE) for patients with benign prostatic hyperplasia (BPH) to treat lower urinary tract symptoms (LUTS) and report their feasibility, safety, and short-term effectiveness. Materials and Methods: 110 patients (mean age: 72.6 years) with BPH related to LUTS were divided into two groups, PAE was performed in one group with 250 - 355 μm non-spherical PVA particles. Whereas, the other group received a mixture of NBCA glue/ lipiodol for PAE. Results: PAE was technically successful in all 110 patients (100 %). During 6 months follow up, we found that in patients who received NBCA glue, the mean of prostatic volume (PV) was significantly reduced compared to baseline (67.1 ± 8.5 to 40.2 ± 5.4), International Prostate Symptom Score (IPSS) (25.7 ± 4.3 to 7.2 ± 1.09), Quality of life (QoL) (4.43 ± 0.27 to 1.58 ± 2.27); whereas, the mean of Peak urinary flow (Qmax) increased significantly from baseline to 6 months (8.6 ± 2.3 to 15.4 ± 2.3), International Index of Erectile Function (IIEFS) (9.46 ± 1.51 to 19.3 ± 1.33). Meanwhile, non-spherical PVA particles used in the other group show that PV significantly reduced from baseline to 6 months (68.2 ± 8.32 to 38.8 ± 6.13), IPSS (25.0 ± 3.59 to7.24 ± 0.83), QoL (4.43 ± 0.24 to1.56 ± 0.55). The mean for Qmax increased from baseline to 6 months (7.19 ± 1.67 to15.1 ± 2.42), IIEFS (9.22 ± 1.30 to 19.5 ± 0.96). Conclusion: PAE with NBCA glue and non-spherical PVA particles is feasible, safe, and effective for patients with BPH related-LUTS. This gives the physicians options to choose between embolizing agents based on the architecture of the prostatic artery.